Aquaporin-4, Connexin-30, and Connexin-43 as Biomarkers for Decreased Objective Sleep Quality and/or Cognition Dysfunction in Patients With Chronic Insomnia Disorder - Yang, Shuai; Kong, Xiao-Yi; Hu, Ting; Ge, Yi-Jun; Li, Xue-Yan; Chen, Jun-Tao; He, Shuo; Zhang, Ping; Chen, Gui-Hai (Frontiers in Psychiatry, 2022)
Objectives To examine serum concentrations of aquaporin-4 (AQP4), connexin-30 (CX30), connexin-43 (CX43), and their correlations with cognitive function in the patients with chronic insomnia disorder (CID). Methods We enrolled 76 subjects with CID and 32 healthy controls (HCs). Serum levels of AQP4, CX30, and CX43 were measured by enzyme-linked immunosorbent assays. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) and polysomnography, and mood was evaluated with 17-item Hamilton Depression Rating Scale and 14-item Hamilton Anxiety Rating Scale. Cognitive function was evaluated by the Chinese-Beijing Version of Montreal Cognitive Assessment (MoCA-C) and Nine Box Maze Test. Results The serum levels of AQP4, CX43, and CX30 were significantly reduced in the CID group compared to the HCs. Partial correlation analysis showed that the biomarkers showed no significant correlations with PSQI score, AHI, ODI and TS90, but AQP4, CX43, and CX30 were positively associated with the percentage and total time of slow wave sleep in the CID group. Serum concentrations of AQP4 and CX30 were positively associated with MoCA-C score in the CID group, and AQP4 level negatively correlated with spatial working memory errors. Conclusions Subjects with CID patients have decreased serum levels of AQP4, CX30, and CX43 indicating astrocyte dysfunction, which could be related to poor objective sleep quality and/or cognition dysfunction.